Impact of Organic Nutrient Management Practices on Yield Attributes, Yield and Economics of Wheat (Triticum aestivum L.) - Parewa, Hanuman Prasad; Ram, Moola; Jain, Lokesh Kumar; Choudhary, Anirudh; Ratnoo, S. D. (International Journal of Bio-resource and Stress Management, 2019)
The field experiment was conducted during rabi 2013-14 and 2014-15 at Agricultural Research Station, Sumerpur, Pali (Rajasthan), India to find out suitable organic nutrient management practices for higher productivity and economics of wheat in Luni basin region of Rajasthan. The experiment was laid out in RBD with seven treatments. The results in terms of growth and yield attributes, grain yield and economics of wheat under different treatments were significantly different than control. Pooled data of two years’ experimentation revealed that the maximum plant height (85.83 cm), number of tillers per meter row length (91.00), number of seed per ear head (55.18), ear head length (9.60 cm), test weight (37.17 g) and grain yield (39.14 q ha-1) were recorded with application of FYM @ 10 t ha-1+Vermicompost @ 1.25 t ha-1 followed by treatment FYM @ 5 t ha-1+Neem green leaves @ 2 t ha-1+Vermicompost @ 1.25 t ha-1. Net return was recorded significantly highest with FYM @ 10 t ha-1+ Vermicompost @ 1.25 t ha-1whereas B:C ratio (2.43) was highest with FYM @ 5 t ha-1+Neem green leaves @ 2 t ha-1+Vermicompost @ 1.25 t ha-1. Application of FYM @ 5 t ha-1+Neem green leaves @ 2 t ha-1+Vermicompost @ 1.25 t ha-1 led to increase grain yield by 94.84% significantly over control (19.0 q ha-1). Hence, the finding suggested that the integration of FYM @ 5 t ha-1+Neem green leaves @ 2 t ha-1+Vermicompost @ 1.25 t ha-1 increased yields of organic wheat in semi arid regions.